Adsorption of chromium from water by carbon nanotubes grown on powdered activated carbon - Al-Mamun, Abdullah; Al-Khatib, Ma An Fahmi Rashid; Jamaluddin Ahmad, Aishah; Al-Sa'adi, Mohammed A.; Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Ismail, Ahmad Faris; Idris, Azni (2009)
Lab-scale experiments were conducted and the adsorption of chromium (Cr) from aqueous solution by using carbon nanotubes (CNTs) grown on powdered activated carbon (PAC). The product is named PACNT. The effects of pH, PACNTs dosage, contact time and initial Cr concentration were studied at ambient room temperature (±25° C) and with a constant agitation of 150 rpm. The statistical optimisation of the experimental conditions was carried out by using Central Composite Design (CCD) to develop the polynomial regression model to determine the optimum operating conditions. The statistical model revealed that the maximum Cr removal (98.5%) was achieved with the optimum condition of pH at 5, initial chromium concentration of 0.08 mg/L, contact time of 80 minutes and PACNTs dosage of 200 mg/L. The PACNTs and PACs were also compared for efficiency in chromium removal. It was revealed that the PACNTs are able to adsorb more Cr compared with the PACs (0.022 mg/L) alone starting with initial chromium concentration of 0.08 mg/L. The final concentration of Cr after the treatment using PACNTs was about 5 ~ 9 times less than that of using PACs alone. Therefore, it can be concluded that CNFs are potential for the adsorption of Cr from water.